2017
DOI: 10.1155/2017/8724503
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Semaphorin3A/Neuropilin-1 Signaling Axis in Apical Periodontitis

Abstract: Apical periodontitis (AP) is a chronic infection of endodontic origin accompanied with bone destruction around the apical region. Semaphorin3A (Sema3A) and neuropilin-1 (Nrp1) are regarded as a pair of immune regulators in bone metabolism. In this study, we firstly investigated the expression pattern of Sema3A/Nrp1 in apical periodontitis and its correlation with bone destruction. Using rat animal model, we analysed the level of mandibular bone destruction and the expression of Sema3A/Nrp1 on days 0, 7, 14, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 26 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…A recent study has found that the expression of SEMA3A and its receptor NRP-1 decreased in a time-dependent manner in mechanical stress-stimulated chondrocytes, and that overexpressing SEMA3A could reduce mechanical stress-induced release of inflammatory cytokines in those chondrocytes [ 20 ]. Moreover, a decline in the expression of SEMA3A/NRP-1 signaling has been reported earlier in rats with periapical lesions as well as patients with apical periodontitis [ 31 ]. Our preliminary investigation found that SEMA3A also had a meaningful expression in LPS-challenged chondrocytes, as its expression decreased with the increase in the duration of LPS stimulation.…”
Section: Discussionmentioning
confidence: 75%
“…A recent study has found that the expression of SEMA3A and its receptor NRP-1 decreased in a time-dependent manner in mechanical stress-stimulated chondrocytes, and that overexpressing SEMA3A could reduce mechanical stress-induced release of inflammatory cytokines in those chondrocytes [ 20 ]. Moreover, a decline in the expression of SEMA3A/NRP-1 signaling has been reported earlier in rats with periapical lesions as well as patients with apical periodontitis [ 31 ]. Our preliminary investigation found that SEMA3A also had a meaningful expression in LPS-challenged chondrocytes, as its expression decreased with the increase in the duration of LPS stimulation.…”
Section: Discussionmentioning
confidence: 75%
“…The role of Sema3A in the regulation of bone remodeling is increasingly recognized [ 36 ] and also includes functions in the periodontium. Lin et al found a reduced expression of Sema3A and Nrp1 in apical periodontitis, which suggests an involvement of Sema3A-dependent signaling in periapical bone resorption [ 37 ]. Using the physiological initiation of bone remodeling in the rat mandible as a model, Hassan et al observed that a temporary loss of Sema3A expression was associated with the migration and activation of osteoclast precursor cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, Sema3A promoted osteoblast differentiation by binding to NRP‐1‐plexin‐A1 receptor complex 26 . A recent study has shown that the expression of Sema3A/ Nrp‐1 significantly decreased in periapical periodontitis patients and rat models of periapical periodontitis, suggesting that Sema3A/Nrp‐1 may contribute to the pathological development of apical periodontitis 27 . In addition, Sema3A‐positive cells were observed in both the dental follicles of developing tooth germs and mature PDL tissue 28 .…”
Section: Introductionmentioning
confidence: 88%